1993
DOI: 10.1128/jb.175.1.214-221.1993
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic repression of anaerobic metabolic systems in Escherichia coli

Abstract: The influence of the osmolarity of the growth medium on anaerobic fermentation and nitrate respiratory pathways was analyzed. The levels of several enzymes, including formate dehydrogenase, hydrogenase, and nitrate reductase, plus a nickel uptake system were examined, as was the expression of the corresponding structural and regulatory genes. While some functions appear to be only moderately affected by an increase in osmolarity, others were found to vary considerably. An increase in the osmolarity of the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…[38]. Gouesbet et al [9] found that about 0.24 M KCl (osmolarity of 820 mOsm) had inhibitory and repressive effects on anaerobic enzymes and the corresponding genes in E. coli due to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…[38]. Gouesbet et al [9] found that about 0.24 M KCl (osmolarity of 820 mOsm) had inhibitory and repressive effects on anaerobic enzymes and the corresponding genes in E. coli due to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate salt concentrations strongly inhibit nitrogen fixation in cyanobacteria by affecting both nitrogenase synthesis and activity (Fernandes et al 1993), and the respiratory nitrate reductase from E. coli is also inactivated by NaCl in a process which can be reversed by glycine betaine (Gouesbet et al 1993). When Rhodococcus sp.…”
Section: Figmentioning
confidence: 97%
“…Although nitrate has been described to be an osmoprotectant in some cyanobacteria (10,28), this is obviously not the case in R. capsulatus E1F1 because of the inhibition of nitrate transport by NaCl. Respiratory nitrate reductase from Escherichia coli is also inactivated by NaCl in a process mediated by intracellular K ϩ which can be reversed by glycine betaine (11).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity is one of the most important factors which can affect microbial and plant growth, and the elucidation of the molecular mechanisms involved in the adaptability to salt stress is the object of current research. Although salinity and osmotic stress have been considered similar phenomena (11,17,21,26), each has different components (10).…”
mentioning
confidence: 99%